A miniaturized reconfigurable antenna for modern wireless applications with broadband and multi-band capabilities - Benkhadda, Omaima; Reha, Abdelati; Saih, Mohamed; Chaji, Kebir; Sarosh, Ahmad; Singh, Harbinder; Al Gburi, Ahmed Jamal Abdullah (Electromagnetics Academy, 2024)
A miniaturized frequency reconfigurable antenna, designed with a simple geometric layout on an FR-4 substrate measuring 15 × 21 mm2, offers versatility for various wireless applications is proposed in this paper. By adjusting biasing conditions of integrated PIN diodes, the antenna can operate in three distinct modes: wideband, dual band, and triband configurations. The antenna demonstrates satisfactory gain and presents an omnidirectional radiation pattern. Verification of the antenna’s functionality involved building a prototype and subjecting it to testing. The confirmed compatibility of the antenna with modern wireless requirements, including the need for small antennas capable of operating across multiple bands and modes, is substantiated by the close agreement between simulated and measured results.